A preliminary study of sexual dimorphism and hermaphroditism occuring in the mudclam sp., Austriella corrugata (Deshayes, 1843). - Dideles, Kristi Marie Joie Fernandez (2005.)
Austriella corrugata, commonly known as imbaw laki, inhabits the muddy bottom of mangrove areas, or the adjacent mudflats. To date, there is only one reported study regarding this clam which is a potential aquaculture species. Further research on the biology and distribution of this clams can greatly contribute to the recognition of this species as an important source of food and income. Thus this study was conducted to gather preliminary investigation on the characterization of imbaw laki. Sexual dimorphism was found to be exhibited by A. corrugata which was determined by its shell morphology and gonad characterization. Maturity rates were laso determined through gonadal biopsy and was noted to be constant throughout the sampling months. Monthly maturity rates was also correlated with the GSI values of the clams. Hermaphroditism was also found to be present in the clam population which was also determined through gonadal biopsy and histological examination of gonad sections.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Mudclam -- Sexual Dimorphism; Mudclam -- Hermaphroditism; Austriella corrugata